Effect of the 32nd-year Soil Tillage and Nitrogen Fertilization on the Population and Biomass of Earthworm under Zea mays L. - Prasetyo, Dedy; Imaria, Dwi; Niswati, Ainin; Yusnaini, Sri (UNIVERSITY OF LAMPUNG, 2021)
The abundance and biomass of earthworms are affected by soil tillage and fertilization. This research aimed to study long-term 32nd-year soil tillage and nitrogen fertilization on the population and biomass of earthworms under Zea mays L. The research was conducted using a randomized block design (RBD) which consisted of two factors. The first factor was the soil tillage that was Intensive Tillage (IT), Minimum Tillage (MT), and No-Tillage (NT). The Second factor was nitrogen fertilization that was N0 = 0 kg N ha-1 and N1= 200 kg N ha-1. Data of earthworm population and biomass were tested using analysis of variance and continued with the least significant difference (LSD) test at the 95% significant level. The population and biomass of earthworms at MT or NT were higher than IT. The population and biomass of earthworms in the plots without fertilization were higher than those at 200 kg N ha-1. There was an interaction between the soil tillage and N fertilization on earthworm biomass observed 60 days after planting at a 0-10 cm depth. There was a positive correlation between soil pH and earthworm population and biomass before the tillage phase.